EDUCATIONAL ONLINE GAME FOR STUDYING VOCABULARY: WORDWALL ON PUPILS’ PERCEPTIONS - Khasanah, Wanda Putri; Ratna Prasasti Suminar (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2023)
Wordwall is an educational online platform that can be applied to pupils’ learning activities. Since it is a game-based application, Wordwall is known as media for building pupils’ interest in learning sessions. This qualitative research targeted to elaborate on pupils’ perception of Wordwall as an online game-learning application for gaining vocabulary mastery. It used questionnaires to collect the data from 36 pupils as participants. There were 3 topics of pupils’ perception examined in this investigation. They were feeling, engagement, and effect. The data findings concluded that most of the students gave positive responses to the learning media. They gave a score of 80.5 % of positiveness to it. It was proven that Wordwall created motivation for pupils in the process of learning vocabulary. Also, the pupils stated that the learning tool had good effects and they always enjoyed it, waited, and did not want to skip playing the online game web.  Nevertheless, there was a neutral result found in the pupils’ focus on the context of the question given in Wordwall, which pointed to no significant effect appearing in pupils for this part.